PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE TONG SUSU PEKANBARU - Tuti Allawiyah; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted at the Tong Susu Cafe Pekanbaru. This study aims to determine the effect of product quality and pricing on purchasing decisions at Cafe Tong Susu Pekanbaru. In this study using quantitative descriptive analysis method and SPSS version 28. The population in this study were all visitors who were visiting Cafe Tong Susu Pekanbaru. Sampling was determined by accidental sampling technique using the Slovin formula and obtained a total sample of 96 respondents. Data collection techniques through questionnaires. The types and sources of data used are primary data and secondary data.The problem in this study is the decline in sales at the Pekanbaru milk keg cafe in the last one year. It can be seen from the visitor and sales data as well as the value score table given by the consumer. From the results of the tests conducted, it shows that the influence of product quality and pricing has a positive and significant effect on purchasing decisions at Cafe Tong Susu Pekanbaru. Keywords: Product Quality, Pricing, Buying Decision